Strengthening Pancasila Values through Conventional Traditional Wisdom - Iskandarsyah Siregar (Lakhomi Journal Scientific Journal of Culture, 2023)
The long process of economic modernization and political democracy in Indonesia has changed the face of Indonesian society, making it more focused on the industrial sector but has still not succeeded in moving the people's economic sector effectively. However, the dynamics of democratic politics in Indonesia are still far from the ideal mandated by the Pancasila deliberative values. Recent political and economic changes, such as development policies that pay less attention to local wisdom and increasingly widespread political liberalization, have had a negative impact on Indonesia's cultural diversity and identity. This research aims to rebuild understanding of local knowledge and political values held by various ethnic groups and communities in Indonesia, with the hope of discovering potential social capital that can be used to improve democratic political practices. The focus of this research is divided into two main aspects: first, analysis of ethnic groups with an emphasis on the Wajo and Minang tribes, and second, a review of several communities living in city parks on the island of Java. The theoretical approach applied is consultative democracy theory, which focuses on the importance of deliberation in the political decision-making process. Within the framework of political anthropology, this research is considered a case study that aims to understand more deeply the dynamics of local politics, as well as the cultural values contained therein. The research method used is qualitative-interpretive, which allows researchers to explore hidden meanings and understandings in the views and experiences of research subjects. Thus, it is hoped that this research will make an important contribution in strengthening the cultural and social foundations for more inclusive and sustainable democratic political practices in Indonesia